Data from: Sympatry and parapatry among rocky reef cichlids of Lake Victoria explained by female mating preferences - Svensson, Ola; Woodhouse, Katie; Smith, Alan; Seehausen, Ole; Turner, George F (University of Borås, 2024)
Work on the Lake Victoria cichlids Pundamilia nyererei (red dorsum males, deeper water), Pundamilia pundamilia (blue males, shallower water) and related species pairs has provided insights into processes of speciation. Here, we investigate female mating behaviour of five Pundamilia species and four of their F1-hybrids through mate choice trials and paternity testing. We discuss the results in the context of the geography of speciation and coexistence. Complete assortative mating was observed among all sympatric species. Parapatric species with similar depth habitat distributions interbred whereas other parapatric and allopatric species showed complete assortative mating. F1-hybrids mated exclusively with species accepted by females of the parental species. Although consistent with reinforcement in sympatry, a closer look at our results suggests otherwise and it is more likely that pre-existing female preferences influence which taxa can co-exist in sympatry. Regardless of the mechanism, mating preferences may influence species distribution in potentially hybridizing taxa, such as in the adaptive radiations of cichlid fish. We suggest that this at least partly explains why some species fail to establish breeding populations in locations where they are occasionally recorded. Our result support the notion that mating preferences of potentially cross-breeding species ought to be included in coexistence theory.

Supplementary tables S1-S3The supplementary tables contain all microsatellite paternity analyses of the wild type females and F1-females used in the present study.Table S1 contains a summary of the spawning decisions of all females, including their IDs. Table S2 includes the microsatellite genotype of all males used in the experiment as well as in which experimental round they were used. The experimental rounds were approximately four weeks each. The experiment was carried out over two years, from August 2006 to July 2008. Table S3 includes microsatellite raw data of the offspring of the females, as well as the paternity analyses. The first row with the ID shows the genotype of the females whereas the following rows with the same ID show the IDs of the offspring. Brood No is the ID of the brood and the rows below, until the next Brood number, are siblings from the same brood. When available, number of eggs in the brood, the size of the brooding female, the date when the female was stripped of eggs/fry and the number and starting date of the experimental round are given on the same row as Brood No. A slash between potential fathers of the same species show that it was not possible to dettermine parentage between the two conspecific males. Fathers within brackets show that the conspecific male is a potential father. However, it is a less likely father e.g. because short time in the experimental setup. Note that all offspring were 100% assigned to one species only. Empty cells are marked with n/a.

Species included in the present study:P. azurea, Ruti IslandP. igneopinnis, Igombe IslandP. nyererei, Makobe IslandP. pundamilia, Makobe IslandP. sp. red head, Zue Island

Table S1. Spawning decisions of wild type females and F1 hybrid femalesTable S2. Microsatellite genotypes and experimental round of malesTable S3. Microsatellite genotypes and paternity analyses

Supplementary figures S1-S2Supplemental figure S2a. ‘melanic’ v. ‘red dorsum’ and ‘blue’ F1-crosses. In the P. azurea x P. nyererei cross (both directions) approximately three fourth were ‘red dorsum’ morphs and one fourth of the crosses were ‘blue’ morphs. The same was true for the P. igneopinnis x P. nyererei cross (both directions). In the latter we followed 26 randomly picked males to old age and the ratio did not change (20 ‘red dorsum’ v. 6 ‘blue’). One male and one female produced the cross except where noted (mother 1, mother 2). We do not have a photo of the P. igneopinnis x P. nyererei, ‘blue’ morph. Photos: Katie Woodhouse.

Supplemental figure S2a. ‘melanic’ v. ‘red dorsum’ and ‘blue’ F1-crosses. In the P. azurea x P. nyererei cross (both directions) approximately three fourth were ‘red dorsum’ morphs and one fourth of the crosses were ‘blue’ morphs. The same was true for the P. igneopinnis x P. nyererei cross (both directions). In the latter we followed 26 randomly picked males to old age and the ratio did not change (20 ‘red dorsum’ v. 6 ‘blue’). One male and one female produced the cross except where noted (mother 1, mother 2). We do not have a photo of the P. igneopinnis x P. nyererei, ‘blue’ morph. Photos: Katie Woodhouse.

Supplemental figure S2b. ‘blue’ v. ‘red chest’ and ‘red dorsum’ F1-crosses. One male and one female produced the cross except where noted (mother 1, mother 2). We do not have photos of the P. pundamilia x P. nyererei and P. sp. ‘red head’ x P. pundamilia crosses. Photos: Katie Woodhouse and Ola Svensson.

Figures S1-2. Experimental set-up and photos of F1 hybrid males

The dataset was originally published in DiVA and moved to SND in 2024.

Work on the Lake Victoria cichlids Pundamilia nyererei (red dorsum males, deeper water), Pundamilia pundamilia (blue males, shallower water) and related species pairs has provided insights into processes of speciation. Here, we investigate female mating behaviour of five Pundamilia species and four of their F1-hybrids through mate choice trials and paternity testing. We discuss the results in the context of the geography of speciation and coexistence. Complete assortative mating was observed among all sympatric species. Parapatric species with similar depth habitat distributions interbred whereas other parapatric and allopatric species showed complete assortative mating. F1-hybrids mated exclusively with species accepted by females of the parental species. Although consistent with reinforcement in sympatry, a closer look at our results suggests otherwise and it is more likely that pre-existing female preferences influence which taxa can co-exist in sympatry. Regardless of the mechanism, mating preferences may influence species distribution in potentially hybridizing taxa, such as in the adaptive radiations of cichlid fish. We suggest that this at least partly explains why some species fail to establish breeding populations in locations where they are occasionally recorded. Our result support the notion that mating preferences of potentially cross-breeding species ought to be included in coexistence theory.

Supplementary tables S1-S3The supplementary tables contain all microsatellite paternity analyses of the wild type females and F1-females used in the present study.Table S1 contains a summary of the spawning decisions of all females, including their IDs. Table S2 includes the microsatellite genotype of all males used in the experiment as well as in which experimental round they were used. The experimental rounds were approximately four weeks each. The experiment was carried out over two years, from August 2006 to July 2008. Table S3 includes microsatellite raw data of the offspring of the females, as well as the paternity analyses. The first row with the ID shows the genotype of the females whereas the following rows with the same ID show the IDs of the offspring. Brood No is the ID of the brood and the rows below, until the next Brood number, are siblings from the same brood. When available, number of eggs in the brood, the size of the brooding female, the date when the female was stripped of eggs/fry and the number and starting date of the experimental round are given on the same row as Brood No. A slash between potential fathers of the same species show that it was not possible to dettermine parentage between the two conspecific males. Fathers within brackets show that the conspecific male is a potential father. However, it is a less likely father e.g. because short time in the experimental setup. Note that all offspring were 100% assigned to one species only. Empty cells are marked with n/a.

Species included in the present study:P. azurea, Ruti IslandP. igneopinnis, Igombe IslandP. nyererei, Makobe IslandP. pundamilia, Makobe IslandP. sp. red head, Zue Island

Table S1. Spawning decisions of wild type females and F1 hybrid femalesTable S2. Microsatellite genotypes and experimental round of malesTable S3. Microsatellite genotypes and paternity analyses

Supplementary figures S1-S2Supplemental figure S2a. ‘melanic’ v. ‘red dorsum’ and ‘blue’ F1-crosses. In the P. azurea x P. nyererei cross (both directions) approximately three fourth were ‘red dorsum’ morphs and one fourth of the crosses were ‘blue’ morphs. The same was true for the P. igneopinnis x P. nyererei cross (both directions). In the latter we followed 26 randomly picked males to old age and the ratio did not change (20 ‘red dorsum’ v. 6 ‘blue’). One male and one female produced the cross except where noted (mother 1, mother 2). We do not have a photo of the P. igneopinnis x P. nyererei, ‘blue’ morph. Photos: Katie Woodhouse.

Supplemental figure S2a. ‘melanic’ v. ‘red dorsum’ and ‘blue’ F1-crosses. In the P. azurea x P. nyererei cross (both directions) approximately three fourth were ‘red dorsum’ morphs and one fourth of the crosses were ‘blue’ morphs. The same was true for the P. igneopinnis x P. nyererei cross (both directions). In the latter we followed 26 randomly picked males to old age and the ratio did not change (20 ‘red dorsum’ v. 6 ‘blue’). One male and one female produced the cross except where noted (mother 1, mother 2). We do not have a photo of the P. igneopinnis x P. nyererei, ‘blue’ morph. Photos: Katie Woodhouse.

Supplemental figure S2b. ‘blue’ v. ‘red chest’ and ‘red dorsum’ F1-crosses. One male and one female produced the cross except where noted (mother 1, mother 2). We do not have photos of the P. pundamilia x P. nyererei and P. sp. ‘red head’ x P. pundamilia crosses. Photos: Katie Woodhouse and Ola Svensson.

Figures S1-2. Experimental set-up and photos of F1 hybrid males

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data from: Sympatry and parapatry among rocky reef cichlids of Lake Victoria explained by female mating preferences
Keywords: coexistence theory; coexistence theory; mate choice; mate choice; reproductive isolation; reproductive isolation; Teacher Education and Education Work; Teacher Education and Education Work; adaptive radiation; adaptive radiation; range expansion; range expansion; hybridization; hybridization; Zoology; Zoologi; Genetics and Genomics; Genetik och genomik; Ecology; Ekologi; Evolutionary Biology; Evolutionsbiologi